LOMBOK WOMAN EMPOWERMENT IN THE DIGITAL ERA THROUGH MANAGING COMMUNITY RADIO AS A MEDIA OF PANDEMIC COMMUNICATION - Athik Hidayatul Ummah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Women have some part in the pandemic Covid-19, especially in providing true information. This article tends to describe how Lombok woman empower themselves through managing community radio during Pandemic Covid-19. Related to the role of community radio is increasing especially in providing the true information needed by the public. These women manage the radio community called “Nina Bayan” in North Lombok Regency. This phenomenon is interesting to be studied since the people in this area have been facing long-standing difficulties, from the Lombok earthquake that occurred in 2018 to the Covid-19 pandemic in 2020. The resilience of society, especially women's groups, in facing this difficult situation is to form a media broadcast which is community radio. The purpose of the research is to explore the role and strategy of the radio community “Nina Bayan” in building pandemic communication during the digital era managed by these women. This study uses a qualitative approach to describe the phenomenon of the study in depth and detail. Research data obtained from interviews (three interviewees: founder, program manager, announcer or teacher), observations and literature review to strengthen the study in theory and methodology. The results show that (1) Dissemination of pandemic communication was packed through the communication media of the radio based on community needs and local wisdom so that it was easily accepted and accessed by the community. (2) The strategy carried out by the radio community to survive amid the challenges of the broadcasting world is capacity building for radio managers and broadcasters, using an inclusiveness approach, creating programs based on community needs and broadcasting digitalization.